Self-Regulation as a Control of Consumptive Behavior - Ratnamaya, Ni Putu Dinda Cetta; Dewi, Ni Luh Yulyana (Pasundan Social Science Development, 2025)
This study aims to examine the role of self-regulation as a key psychological mechanism in controlling impulsive and compulsive consumer behavior, particularly in the context of digital media influence. The objectives of the study were to determine how self-regulation influences consumer decision-making, analyze the interaction between intrapersonal communication and self-regulation, and propose strategies to reduce excessive consumer behavior among adolescents and young adults. The research method used a systematic literature review by analyzing scientific articles from various databases such as Google Scholar, ScienceDirect, ProQuest, and ResearchGate published in the last ten years. Data collection was carried out through keyword searches related to "self-regulation," "impulse buying," "consumer behavior," and "digital influence," then selected based on relevance and quality. Data were analyzed using content analysis methods on 35 selected studies, which showed that individuals with high self-regulation are able to resist impulsive stimuli through a process of internal reflection and rational intrapersonal communication. The results revealed that self-regulation functions as a key buffer against impulsive buying, especially when supported by intrapersonal communication strategies. The implications of these findings are important for policymakers and practitioners in developing programs to improve self-regulation skills to control excessive consumption. Further research is recommended using experimental approaches and longitudinal studies to test the effectiveness of interventions. This study references 45 scientific literature, includes tables and graphs illustrating key relationships, and makes recommendations for future studies.